Ultrasound-guided synovial biopsy: a safe, well-tolerated and reliable technique for obtaining high-quality synovial tissue from both large and small joints in early arthritis patients. Issue 3 (13th December 2013) - Kelly, S; Humby, F; Filer, A; Ng, N; Di Cicco, M; Hands, R E; Rocher, V; Bombardieri, M; D'Agostino, M A; McInnes, I B; Buckley, C D; Taylor, P C; et al.
Abstract : Objective: To determine the tolerability, safety and yield of synovial tissue in an early arthritis cohort using a minimally invasive, ultrasound (US)-guided, synovial biopsy technique in small, medium and large joints. Methods: 93 sequential biopsy procedures were assessed from a total of 57 patients (baseline and 36 repeat biopsies at 6 months) recruited as part of the 'Pathobiology of Early Arthritis Cohort' study. Patients completed a tolerability questionnaire prior to and following the synovial biopsy procedure. The synovial biopsy was performed under US guidance with US images of the joint recorded prior to each procedure. Synovial tissue was harvested for immunohistochemistry and RNA extraction. Results: Five different joint sites were biopsied (knee, elbow, wrist, metacarpal phalangeal and proximal interphalangeal). No significant complications were reported following the procedure. No difference in pain, swelling and stiffness of the biopsied joint from before and after the procedure was demonstrated. A median of 14 biopsy samples was retrieved from each procedure with 93% of biopsy procedures yielding good quality tissue. RNA yield was good in all joints and in repeat biopsies. Multivariant analysis demonstrated a significantly greater yield of RNA and graded tissue in relation to a high prebiopsy, grey-scale synovitis score (0–3, semiquantitative). Conclusions: A minimally invasive approach to synovial tissue harvesting, using US guidance, is both safe and well-tolerated by patients. Tissue quality/RNA yield is preserved in subsequent biopsies following therapeutic intervention. A high US grey-scale synovitis score is a predictor of good quality/quantity of tissue and RNA.